2020
DOI: 10.1111/jdv.16834
|View full text |Cite
|
Sign up to set email alerts
|

Perianal warts as a risk marker for anal high‐risk‐human papillomavirus (HPV) detection and HPV‐associated diseases

Abstract: Background Genital warts are the most common sexually transmitted infection (STI) and are caused by human papillomavirus (HPV). Persistent anal infection by oncogenic genotypes of HPV is a determinant for anal cancer. Currently, anal cancer screening is not widely implemented. Objectives Our aim is to evaluate the role of perianal warts as a risk marker for anal high-risk (HR) HPV detection and anal dysplasia. Methods In this observational, retrospective, cohort study of attendees of a STI outpatient clinic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…16 Although associated with LR-HPV 6 and 11, genital warts could harbour HR-HPV as well as premalignant and malignant tumours. 9,17,18 As expected, we found that the presence or history of anogenital warts seems to be associated with positive HPV-DNA neoplasia.…”
Section: Discussionsupporting
confidence: 86%
“…16 Although associated with LR-HPV 6 and 11, genital warts could harbour HR-HPV as well as premalignant and malignant tumours. 9,17,18 As expected, we found that the presence or history of anogenital warts seems to be associated with positive HPV-DNA neoplasia.…”
Section: Discussionsupporting
confidence: 86%
“…In China ( 9 ), the estimated prevalence of anal HPV among MSM was 85.1% (HIV-positive), 53.6% (HIV-negative), and 59.2% (unknown HIV status). Persistent infection with high-risk HPV (Hr-HPV) is a known cause of cervical, head and neck, penile and anal cancers ( 2 , 10 , 11 ), and low-risk HPV (Lr-HPV) can also cause genital warts ( 12 , 13 ). MSM are about 20 times more likely to develop anal cancer than heterosexual men are ( 14 , 15 ), and a recent study showed that HPV was detected in 88.3% of anal cancers ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that physicians are probably recommending more of these procedures to PLWH with genital warts. Although genital warts are caused by low-risk HPV types, individuals with anal warts are at increased risk of anal cancer [ 31 33 ]. We also found that, unlike previously published findings [ 34 36 ], that fear, embarrassment, and cost were not common barriers reported by the participants in our study.…”
Section: Discussionmentioning
confidence: 99%